THE IMPACT OF THE MODERNIZATION PROCESS ON TRADITIONAL VALUES - Elyor Shavkatovich Oripov; Sharifjon Shokiralievich Khudoyberganov (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, subject to the dialectical analysis of the following: the need for support on the basis of traditional values in the implementation of reforms in the process of modernization of the society, the possibility of gaining national independence of each nation only by relying on a system of values formed through the centuries, social and philosophical aspects of the impact of social and political modernization on the nature and content of traditional values.